Modul Android Berbasis Keterampilan Proses Sains Terintegrasi Nilai-Nilai Islam untuk Siswa Sekolah Dasar - Wiratman, Arwan; Bungawati, Bungawati; Widianti, Nadila (Jurnal Riset dan Inovasi Pembelajaran, 2025)
This study aims to develop Android modules based on science process skills integrated with Islamic values that are valid and practical to improve the quality of science learning in elementary schools. This study used the Research and Development method with the Multimedia Development Life Cycle (MDLC) design to develop Android modules based on science process skills integrated with Islamic values. This research involved 3 experts and 23 fourth-grade students of State Elementary School 54 Salupikung Palopo City. Data collection techniques included observation, interview, and questionnaire using a Likert scale to measure the validity and practicality of the module. The data obtained were analyzed by calculating the percentage of feasibility and interpreted qualitatively based on the module validity and practicality criteria. The results showed that the Android module based on science process skills integrated with Islamic values met the needs of students. This module obtained very good validity from material, language, and media experts and was rated very practical by students in terms of ease of use and learning benefits. The integration of science and Islamic values in this module helps students understand the material of Light Energy deeply, strengthen their character, and understand the connection between science and religion.